2012
DOI: 10.1308/003588412x13171221591736
|View full text |Cite
|
Sign up to set email alerts
|

Survey of UK practice for management of breast cancer metastases to the neck

Abstract: INTRODUCTIONCervical metastases from breast carcinoma are rare and their management is controversial. Between 1987 and 2002 the American Joint Committee on Cancer (AJCC) staged patients with supraclavicular fossa nodal disease as M1 but the subsequent demonstration that patients with regional stage IV disease had better outcomes than visceral stage IV disease led to a reclassification of the former to stage IIIC in 2003. The literature remains inconsistent regarding the fate of these patients. Despite the atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The question remains whether upper and middle jugular vein lymph node (levels II and III) metastases represent distant disease as opposed to isolated supraclavicular metastases. Contrary to the current staging system, Bisase and Kerawala conducted a survey in the United Kingdom regarding the management of breast carcinoma that had metastasized to the neck, 61% of those interviewed clinicians felt that both level V and III neck metastases represent incurable stage IV disease.…”
Section: Specific Primary Tumor Sitesmentioning
confidence: 98%
See 1 more Smart Citation
“…The question remains whether upper and middle jugular vein lymph node (levels II and III) metastases represent distant disease as opposed to isolated supraclavicular metastases. Contrary to the current staging system, Bisase and Kerawala conducted a survey in the United Kingdom regarding the management of breast carcinoma that had metastasized to the neck, 61% of those interviewed clinicians felt that both level V and III neck metastases represent incurable stage IV disease.…”
Section: Specific Primary Tumor Sitesmentioning
confidence: 98%
“…However, given the low frequency of supraclavicular metastases, there is no consensus regarding optimal treatment. Bisase and Kerawala concluded that there is a widespread inconsistency in the management of such patients, but there was a trend toward aggressive surgical treatment, including recommendations for comprehensive neck dissection despite the lack of high‐level evidence. After a neck dissection, there was also no agreement as to whether giving adjuvant treatment was necessary, but the prognosis in general was better in cases managed by combined adjuvant therapies …”
Section: Specific Primary Tumor Sitesmentioning
confidence: 99%
“…After this report, patients with supraclavicular lymph node involvement were downgraded to stage IIIB. Bisase et al concluded from a survey of 117 head and neck surgeons in United Kingdom that there is wide-spread inconsistency in patients' management with cervical metastases of mammary cancer, but there was a trend towards aggressive surgical treatment despite the lack of high-level evidence [18]. In a recent retrospective study based on 78 Korean patients with ipsilateral supraclavicular lymph node metastases of mammary cancer, it was revealed that neck dissection did not improve loco-regional or disease free survival [19].…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that neck metastasis simply represents a transitional step between extended regional spread and true distant metastasis, or that those patients were diagnosed earlier in the course of the disease, which in fact prolongs survival. In the survey performed by Bisase and Kerawala [25] in the UK in 2016 regarding the treatment of breast carcinoma neck metastases, 61% of the participants considered level V in the neck, as well as level III, as a disease that cannot be cured. In contrast, aggressive treatment with curative intent was proposed for contralateral axillary metastases [26][27][28][29]; also, fewer supraclavicular and neck metastases were detected with more aggressive primary surgical treatment [30].…”
Section: Discussionmentioning
confidence: 99%